Indeks kualiti air di sekitar kawasan lombong di Pelepah Kanan, Kota Tinggi Johor - Wan Mohd Razi Idris,; Sahibin Abdul Rahim,; Zulfahmi Ali Rahman,; Tukimat Lihan,; Mohd Talib Latif,; Low, Yiak Chong; Azman Hashim,; Shahrinizam Mohd Yuuof, (Universiti Kebangsaan Malaysia, 2009)
This study was carried out to determine the water quality index at the Pelepah Kanan River, Kota Tinggi, Johor. Six stations were chosen from different part of the river from upstream to downstream to represent the water quality index along this river. Three replicates of samples were taken from each station. Samples were collected in two different seasons namely dry season (July) and rainy season (December) 2007. In-situ physico-chemical measurements included temperature, pH, dissolved oxygen and conductivity. Physico-chemical parameters determined in the laboratory were turbidity, total suspended solid (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD) and ammonia nitrogen (NH3-N). According to the Interim National Water Quality Standards (INWQS), results showed that all sampling stations along the Pelepah Kanan River in July fall in Class I-II for physical and chemical parameters except for dissolved oxygen and pH which was in Class I-II. The results obtained in December also showed that all sampling stations fall in Class I for physical and chemical parameters except for pH which was in Class III. Correlation test showed that some physico-chemical parameters have significant correlation with each other. Water Quality Index (WQI) analysis showed that the mean WQI value for the month of July is 96.88 (Class I) while for December, the WQI value deteriorated to 84.03 (Class II). According to the calculated values of WQI and comparison with INWQS, the index of water quality in Pelepah Kanan River is in the clean category and is not affected by pollution neither anthropogenic activities nor natural pollution.